Implementación de un sistema electrónico convertidor de texto a lenguaje braille dirigido a personas con discapacidad visual - Orna Carguacundo, Danilo Alexander (2024)
Visual disability is a topic of great interest in today's society since it is one of the most frequent disabilities suffered by children and adults. For this reason, large global organizations constantly carry out research on how to improve and help these people feel more integrated into society. That is why electronic equipment can convert text to Braille language, and this project was born. This research aims to construct electromechanical equipment capable of converting text to braille language for people with visual disabilities. It was carried out in five phases, starting with a prior study of the Braille language and the existing technologies. The prototype design process was then determined with simulation and design software for the mechanical, electronic, and logical parts. Subsequently, following the same conventional structure of the braille cell, three cell prototypes were made: small, medium, and large. Once the prototypes were assembled, the respective field tests were carried out with a group of people belonging to the Dr. Luis Benavides Specialized Educational Unit. Finally, a statistical analysis was carried out where it was determined that the size of the cells does not affect their correct functionality; however, the level of knowledge of the language does significantly infer since it was evident that a person who is an expert in the language braille had 0% error, an average level person 12% and a novice student in braille 38.53%.